Fuzzy Logic Tool to Forecast Soil Fertility in Nigeria - G. O. Ogunleye; S. G. Fashoto; Petros Mashwama; S. A. Arekete; O. M. Olaniyan; B. A. Omodunbi (The Scientific World Journal)
The soil is composed of several nutrients which are important for the effective growth of plants. Nitrogen, phosphorus, and potassium are micronutrients which are very important for plant growth. There have been several methods and soil tests developed to test the compositions of these nutrients in the soil. Interpreting the results gotten from such tests has been a herculean task for farmers. Employing the use of a soft computing method to interpret such result would be a noble idea. In this paper, we describe the use of fuzzy logic to interpret the values of nitrogen, phosphorus, and potassium (NPK) gotten from conventional soil test to know their levels in the soil and predict possible NPK inputs.